Pengaruh kepemimpinan dan lingkungan kerja terhadap kinerja karyawan di inna grand bali beach hotel resort & spa - Wahyuni, Luh Seri; Arismayanti, Ni Ketut; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas; Vol 3 No 2 (2019): Vol.3,No.2,2019, 2019)
ABSTRACT This research was conducted at Inna Grand Bali Beach Hotel Resort & Spa. which aims to determine the influence of leadership and work environment on employee performance at Inna Grand Bali Becah Hotel Resort & Spa. In this study, the independent variables are leadership and work environment while the dependent variable is employee performance. This study uses descriptive quantitative research methods. The technique of collecting data is by observation, interviews, questionnaires, and literature studies. and sampling techniques using quota sampling techniques and proportional random sampling methods. The sample in this study amounted to 125 respondents out of 500 total employees at Inna Grand Bali beach Resort & Spa. Data analysis technique uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F test, T test. Based on the results of research and discussion Simultaneously Leadership variables (X1) and work environment (X2) together have a positive and significant effect on employee performance (Y) at Inna Grand Bali Beach Hotel Resort & Spa. Based on the test results, the significance value of F is equal to 0,000 which is smaller than 0.05 (F <?) which means that the independent variables namely leadership (X1) and work environment (X2) have a significant or simultaneous effect on the dependent variable namely performance employee (Y). It is known that tcount X1 or leadership is 3,896. When compared with the ttable value of 1.980, the tcount obtained is greater than the value of ttable (3.896> 1.980). These results can be interpreted that leadership variables have a positive and significant effect on employee performance. The value of tcount X2 or work environment is 12,066. When compared with the ttable value of 1.980, the tcount obtained is greater than the value of ttable (12.066> 1.980). This result can be interpreted that work environment variables have a positive and significant effect on employee performance (Y).